Records of Jerdon’s baza Aviceda jerdoni (Blyth, 1842) from eastern Nepal - Tamang, Sanjaya Raj; Poudel, Amrit Kumar; Pandeya, Pratik (Nepalese Journal of Zoology, 2021)
Jerdon's baza Aviceda jerdoni is one of the least studied raptor species in Nepal which is listed as a Critically Endangered species in the ‘Nepal's Red List of Birds’. This paper presents the records of this species during opportunistic surveys, conducted in 2018/2019 from Ilam and Jhapa districts of eastern Nepal. A total of 18 individuals were sighted during the study period with the first record of nest of the species in Nepal. The sightings were made between 70 m, the lowest global known range to 1048 m from mean sea level, and the highest altitudinal record for Nepal. Hunting and unintentional prey poisoning were identified as major threats for species in the study site.